Detection of mutations in MYOC, OPTN, NTF4, WDR36 and CYP1B1 in Chinese juvenile onset open-angle glaucoma using exome sequencing - Huang, Chukai (Sci Rep, 2018)
Juvenile onset open-angle glaucoma (JOAG) affects patients before 40 years of age, causing high intraocular pressure and severe optic nerve damage. To expand the mutation spectrum of the causative genes in JOAG, with a view to identify novel disease-causing mutations, we investigated MYOC, OPTN, NTF4, WDR36 and CYP1B1 in a cohort of 67 unrelated Chinese JOAG patients. Whole exome sequencing was used to identify possible pathogenic mutations, which were further excluded in normal controls. After sequencing and the use of a database pipeline, as well as predictive assessment filtering, we identified a total of six mutations in three genes, MYOC, OPTN and CYP1B1. Among them, 2 heterozygous mutations in MYOC (c. 1109C > T, p. (P370L); c. 1150G > C, p. (D384H)), 2 heterozygous mutations in OPTN (c. 985A > G, p.(R329G); c. 1481T > G, p. (L494W)) and 2 homozygous mutations in CYP1B1 (c. 1412T > G, p.(I471S); c. 1169G > A, p.(R390H)) were identified as potentially causative mutations. No mutation was detected in NTF4 or WDR36. Our results enrich the mutation spectra and frequencies of MYOC, OPTN and CYP1B1 in JOAG among the Chinese population. Further studies are needed to address the pathogenicity of each of the mutations detected in this study.